Compatibility of Insecticides and Fungicides Targeting Major Insect Pests and Diseases of Rice - Seni, Atanu; Pal, Rini; Naik, Bhima Sen (International Journal of Bio-resource and Stress Management, 2018)
A field experiment was conducted in the research farm of Regional Research and Technology Transfer Station (OUAT), Chiplima, Odisha, during July to November, 2014 and January to May, 2015. Study was undertaken to determine the compatibility of selected insecticides and fungicides against major pests namely stem borer, plant hopper and diseases; blast and sheath blight of rice. The treatments were; Rynaxypyr 20 SC @ 150 ml ha-1; Dinotefuran 20 SG @ 200 g ha-1; Carbendazim 12% plus mancozeb 63% 75 WP @ 1000 g ha-1; Validamycin 3 SL @ 1250 ml ha-1; their tank mix combination and untreated control. Among the different combinations tested, Rynaxypyr in combination with Carbendazim plus mancozeb recorded less dead heart (1.35%), white ear head (0.92%), blast incidence (0.75%), sheath blight incidence (2.75%) and produced highest yield (43.5 q ha-1) followed by rynaxypyr in combination with validamycin (2.03%, 1.35%, 1.52%, 2.40% and 41.1 q ha-1) and alone rynaxypyr 20 SC (2.2%, 1.23%, 2.66%, 4.2% and 40.3 q ha-1) compared to untreated control. There was no reduction in the efficacy of these insecticides and fungicides when used as tank mix. No phytotoxicity symptoms were observed in treated field. So, all the insecticides and fungicides combinations are compatible with each other and can be safely used as tank mix for the control of simultaneous occurrence of rice pests and diseases, thus, saving the application cost.